2020
DOI: 10.3233/jad-191113
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Alterations of the Temporal Lobe and Hippocampus in Semantic Dementia and Alzheimer’s Disease

Abstract: Background: Semantic memory impairments in semantic dementia are attributed to atrophy and functional disruption of the anterior temporal lobes. In contrast, the posterior medial temporal neurodegeneration found in Alzheimer's disease is associated with episodic memory disturbance. The two dementia subtypes share hippocampal deterioration, despite a relatively spared episodic memory in semantic dementia. Objective: To unravel mutual and divergent functional alterations in Alzheimer's disease and semantic demen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…The anterior hippocampus forms preferential connections to the temporal pole (Kahn et al, 2008) via the uncinate fasciculus (Kier et al, 2004), laying the groundwork for greater functional connectivity at rest (Honey et al, 2009) and during semantic processing (e.g., Hoffman & Morcom, 2018). Indeed, patients with semantic dementia often demonstrate damage and altered intrinsic functional connectivity to both of these regions (e.g., Chan et al, 2001;Schwab et al, 2020). If these regions are recruited to support episodic AM recollection in older adults, such memories might necessarily be "semanticized," or imbued with more semantic information (Spreng et al, 2018).…”
Section: Temporal Pole Volumes Relate To Episodic Am In Older Adultsmentioning
confidence: 99%
“…The anterior hippocampus forms preferential connections to the temporal pole (Kahn et al, 2008) via the uncinate fasciculus (Kier et al, 2004), laying the groundwork for greater functional connectivity at rest (Honey et al, 2009) and during semantic processing (e.g., Hoffman & Morcom, 2018). Indeed, patients with semantic dementia often demonstrate damage and altered intrinsic functional connectivity to both of these regions (e.g., Chan et al, 2001;Schwab et al, 2020). If these regions are recruited to support episodic AM recollection in older adults, such memories might necessarily be "semanticized," or imbued with more semantic information (Spreng et al, 2018).…”
Section: Temporal Pole Volumes Relate To Episodic Am In Older Adultsmentioning
confidence: 99%
“…It is manifested as a deterioration in memory trace consolidation represented by the result in the attempt to freely reproduce after a 20minute deferral in AVLT. [38][39][40] Many researchers have previously confirmed that those were independent predictors of the progression of Alzheimer's disease. [41][42][43][44][45][46] Both AD and AD+D groups were characterized by a lack of memory trace of deferred auditory hearing memory of any form and a significant decrease in memory skills.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the temporal lobe, prefrontal and parietal areas are associated with episodic memory. [38][39][40] The structures involved in the memory formation process are the hippocampus and the structure surrounding the olfactory sulcus. [38][39][40] It is in these areas that the degenerative process takes place at the early stages of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rs-FC network nodes which exhibit significant groupwise difference across HC, MCI, and AD groups. ,10, 11,12,20,21,23,24,25,26,27,35,36,37,39,42,45,47,50, 51, 53, 54, 55, 56, 58, 59, 60, 61, 62, 64, 65, 70, 71, 72, 73, 74, 95, 96, 98, 99, 100, 104, 106, 110, 112, 113, 116, 118, 125 …”
mentioning
confidence: 99%